What Kind of Culture do Poles Need? Antiirrationalism towards the Dilemmas of Civilization - Brożek, Anna (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
„Antiirationalism” is a term which shortly characterizes the Lvov-Warsaw School, a group founded by Kazimierz Twardowski at the turn of the 19th century. In philosophy, which was the main object of interest of the School, antiirrationalism was realized by applying two postulates: the postulate of clearness of language and the postulate of appropriate justification of statements. However, antiirrationalism as a certain attitude goes far beyond the philosophy sensu stricto and reaches various spheres of human activities. In the article, I present some dilemmas of the contemporary civilization which I call “political”, “logical” and “axiological” respectively. Based on various Twardowski’s statements and some facts from the history of the Lvov-Warsaw School, I show what answers to these dilemmas are dictated by the program of antiirrationalism.